The most complete amiid fish from the Coal Creek Member of the Eocene Kishenehn Formation in northwestern Montana - JACOB D. GARDNER; MARK V.H. WILSON (Acta Palaeontologica Polonica, 2022)
The larger-bodied fish fauna of the Kishenehn Formation’s Coal Creek Member (Eocene, 43.5 Ma), northwestern Montana, is understudied because of a sampling bias towards small specimens. Small specimens (<10 cm length) of taxa are usually found as mostly to fully complete compression fossils. Relatively larger-bodied fishes, such as amiids (the bowfin Amia calva and close relatives), are only known from fragmentary remains for which taxonomic resolution is only possible to the family level. Here we describe the most complete amiid fossil (USNM 618000) from the Kishenehn Formation. We assign this specimen to the genus Amia based on the presence of pointed coronoid teeth and a long preural region (81 preural centra). The specimen exhibits a combination of features from multiple species, including a total of 89 centra (like Amia calva and Amia scutata), eight ural centra (like Amia scutata and Amia pattersoni), and a concave anteroventral margin on the first postinfraorbital (like Amia hesperia). The lack of more complete specimens of amiids and other larger-bodied taxa is most often attributed to a preservation bias; however, this could also reflect a rarity of amiids in the ecosystem overall or a partitioning of habitat preference away from the shallow, near-shore regions of the ancient lake. This new specimen enhances the known biodiversity of relatively larger-bodied fishes from this region during the Eocene epoch.